Development of mathematics learning video based on Palembang local wisdom about prism materials - Pitriani, Pitriani (Universitas Islam Negeri Raden Intan Lampung, 2022)
The Palembang local wisdom-based mathematics learning video is a tangible manifestation of the nation's character building through education. The developed video discusses the prism materials for eighth-graders. The video was developed through development research by adopting the ADDIE design into ADD (analysis – design – development). The purpose of the study was to examine the feasibility of learning mathematics videos based on local wisdom from experts’ judgment on material, media, and language. The research instruments were a questionnaire and a suggestion sheet. Assessment of prototype 1 showed that the video is “Feasible Enough” but needs to be improved. After revisions are made, the video is called Prototype 2. The expert’s assessment of Prototype 2 showed that the video is